Current Research Status and Development Trends of Mine Ventilation Technology in China - Zhang, Yi (Scientific Journal of Technology, 2025)
Mine ventilation is a crucial safeguard for safety in mine production. This paper provides an in-depth analysis of the current development status and future trends of mine ventilation technology in China. By reviewing the technological evolution, intelligent transformation practices, breakthroughs in key technologies, and the effectiveness of industry applications, it reveals the core values of mine ventilation systems in ensuring safety, enhancing energy efficiency, and promoting green development. Combining policy guidance, market demands, and directions of technological innovation, the paper indicates that future mine ventilation technology will evolve towards deep intelligence, full-factor digitization, and green and low-carbon development. Furthermore, it proposes development suggestions such as strengthening basic research, improving standard systems, and cultivating interdisciplinary talents, providing theoretical support for promoting safe and efficient mining operations in China.